SELF-EFFICACY THEORY AS A SOLUTION TO THE PROBLEM OF ISLAMIC EDUCATIONAL LEADERSHIP - Hasan Basri; Fajar Syarif; Muhammad Hanif Bin Ali (Jurnal Konseling Pendidikan Islam, 2024)
Islamic educational institutions face increasing leadership challenges in the era of globalization and digital transformation. Issues such as limited leadership innovation, low leadership confidence, and weak decision-making capacity often hinder institutional development and competitiveness. This study aims to examine how Self-Efficacy Theory can serve as a conceptual solution to leadership problems in Islamic educational institutions. The research employs a qualitative approach using library research by analyzing relevant scholarly literature published between 2018 and 2023 on educational leadership, psychological competence, and Islamic education management. The findings indicate that leadership effectiveness is strongly influenced by psychological competence, particularly self-efficacy, which shapes leaders’ confidence, motivation, and persistence in managing organizational challenges. Leaders with strong self-efficacy are more likely to initiate innovation, make strategic decisions, and foster collaborative organizational cultures. The study also identifies four major sources of self-efficacy—mastery experiences, vicarious experiences, social persuasion, and emotional regulation—as key factors in strengthening leadership capacity. Integrating self-efficacy with Islamic leadership values such as responsibility (amanah), perseverance, and spiritual resilience can contribute to the development of adaptive, innovative, and effective leadership in Islamic educational institutions. Therefore, strengthening leaders’ self-efficacy should become an important component of leadership development programs in Islamic education.